Increased Risk of Psychiatric Disorders in Allergic Diseases: A Nationwide, Population-Based, Cohort Study - Tzeng, Nian-Sheng; Chang, Hsin-An; Chung, Chi-Hsiang; Kao, Yu-Chen; Chang, Chuan-Chia; Yeh, Hui-Wen; Chiang, Wei-Shan; Chou, Yu-Ching; Chang, Shan-Yueh; Chien, Wu-Chien (Frontiers in Psychiatry, 2018)
Background/objective: Allergic diseases, such as bronchial asthma, allergic rhinitis, atopic dermatitis, and psychiatric disorders are major health issues. There have been reports that allergic diseases were associated with depression or anxiety disorders. This study aimed to investigate the association between these allergic diseases and the risk of developing overall psychiatric disorders in patients from Taiwan. Methods: This cohort study used the database of the Taiwan National Health Insurance (NHI) Program. A total of 186,588 enrolled patients, with 46,647 study subjects who had suffered from allergic diseases, and 139,941 controls matched for sex and age, from the Longitudinal Health Insurance Dataset of 2000-2015, were selected from a sub-dataset of the National Health Insurance Research Database (NHIRD). Fine & Gray’s competing risk model analysis was used to explore the hazard ratio (HR), and 95% confidence interval (CI), for the risk of allergic diseases being associated with the risk of developing psychiatric disorders during the 15 years of follow-up. Results: Of the study subjects, 5,038 (10.8%) developed psychiatric disorders when compared to 9,376 (6.7%) in the control group, with significant difference (p < 0.001). Fine and Gray's competing risk model analysis revealed that the adjusted HR was 1.659 (95% CI= 1.602 - 1.717, p < 0.001). In this study, we found that the groups of atopic dermatitis alone, and the allergic rhinitis + atopic dermatitis were associated with a lower risk of psychiatric disorders, but all the other four groups, as bronchial asthma alone, allergic rhinitis alone, bronchial asthma + allergic rhinitis, bronchial asthma + atopic dermatitis, and the combination of all these three allergic diseases were associated with a higher risk of psychiatric disorders. Conclusions: Allergic diseases are therefore associated with a 1.66-fold increased hazard of psychiatric disorders in Taiwan.